Pengaruh Rekrutmen, Seleksi dan Pelatihan terhadap Kinerja Karyawan pada Bank Mega Syariah Samarinda - Muhammad Afif Ridha; Muhammad Birusman Nuryadin; Darmawati (Universitas Muhammadiyah Surabaya, 2023)
Employee performance is important in increasing employee productivity. In improving the performance of company employees must be able to know the factors that can affect performance. Several factors that influence employee performance are recruitment, selection, and training. Recruitment, selection and training have a close relationship to employee performance, so this study aims to determine the effect of recruitment, selection and training on employee performance at Bank Mega Syariah in Samarinda City. Furthermore, the results of the study are that partially employee recruitment has a partial negative effect on employee performance with a proven significant value of 0.031 <0.1 and a t-value of -2.651 <t table 1.943. Partial employee selection also has a negative effect on employee performance with a significant value of 0.031 <0.1 and t count -2.651 <1.943. Partial employee training has no positive effect on employee performance with a value of 0.687 > 0.1 and t count 0.423 <1.943. Simultaneously, recruitment, selection and training together have a positive influence on the performance of Bank Mega Syariah Samarinda City employees with a significant value of 0.076 <0.1 and an F count of 3.825 > F table 3.0741.